1985
DOI: 10.1007/bf02133960
|View full text |Cite
|
Sign up to set email alerts
|

Plasma angiotensin I and serum placental leucine aminopeptidase (P-LAP) in pre-eclampsia

Abstract: A study was undertaken on serial measurements of plasma angiotensin I (A-I) and serum placental leucine aminopeptidase (P-LAP) activities in normal and pre-eclamptic pregnancy. There was the significant difference in A-I levels between normal and mild pre-eclamptic pregnancy at weeks 30, 35, 37, between normal and severe pre-eclamptic pregnancy at week 37. There were no differences in serum P-LAP between normal and mild pre-eclamptic pregnancy up to week 33, but thereafter the levels for the mild pre-eclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Cystyl aminopeptidase also has angiotensinase activity and relatively high levels of the enzyme have been found in pregnancy sera in cases of pre-eclampsia and low levels in the late stage of severe pre-eclampsia (181). Serum activities of aspartyl aminopeptidase (aminopeptidase A), which also exhibits angiotensinase activity, show a significant decrease in cases of pre-eclampsia (182).…”
Section: Cystyl Aminopeptidasementioning
confidence: 99%
“…Cystyl aminopeptidase also has angiotensinase activity and relatively high levels of the enzyme have been found in pregnancy sera in cases of pre-eclampsia and low levels in the late stage of severe pre-eclampsia (181). Serum activities of aspartyl aminopeptidase (aminopeptidase A), which also exhibits angiotensinase activity, show a significant decrease in cases of pre-eclampsia (182).…”
Section: Cystyl Aminopeptidasementioning
confidence: 99%
“…It has recently been shown that somatostatin decreases insulin synthesis through a direct inhibitory effect on insulin gene expression [24], Previously, we have shown that the admin istration of bestatin in pregnant rats resulted in IUGR rat fetuses [25]. In addition, we reported a significant positive correlation be tween P-LAP activities in maternal peripheral sera and fetal body weight in normal and severe preeclamptic pregnancies [26], Therefore, further research is needed for the clarification of the relationship between P-LAP activities in maternal sera and the ratio of UA/UV somatostatin levels. We clari fied that a possible new role of P-LAP.…”
Section: Ig F -Iimentioning
confidence: 69%
“…Maternal serum APA and P-LAP activities in early mild preeclampsia patients are higher than those seen in normal pregnancy patients (Mizutani et al, 1985c;Safwat et al, 1995). As the severity of preeclampsia progresses both APA and P-LAP enzyme activities decrease, ultimately becoming lower than that measured during normal pregnancy (Mizutani et al, 1985c(Mizutani et al, , 1987. It is likely that increased APA and P-LAP activities in maternal sera before, and immediately after, the appearance of preeclampsia is in response to the increased production of AngII/AVP from the fetus.…”
Section: The Importance Of Placental Aminopeptidasesmentioning
confidence: 92%